Anterior cruciate ligament remnant and its values for preservation - Takeshi Muneta; Hideyuki Koga (Elsevier, 2017)
Controversy surrounds the remnant-preserving anterior cruciate ligament surgery. Advantages of remnant preservation have been reported in regard to better healing and knee function, although no consensus has been reached. This review article discussed the value and meaning of anterior cruciate ligament remnant preservation in several sections such as effects on healing, remnant classification, biomechanical evaluation, relation to proprioception, animal studies, and clinical studies. We hope that this review will facilitate further discussion and investigation for better treatment of anterior cruciate ligament injuries. So far, the current reviews have not provided sufficient scientific evidence to support the value of preserving the remnant.